Explorating the Involvement of Plasma Sestrin2 in Obstructive Sleep Apnea - Rong Jiang; Qiru Wang; Huifen Zhai; Xiaohua Du; Shibo Sun; Haoyan Wang (Canadian Respiratory Journal)
Obstructive sleep apnea (OSA) can lead to serious complications such as coronary heart disease and hypertension due to oxidative stress. Sestrin2 expression is upregulated under conditions of oxidative stress. This study aimed to explore whether Sestrin2 was involved in OSA. OSA and healthy control subjects were recruited and matched with age, gender, and body mass index (BMI). Plasma Sestrin2 levels were measured and compared. A multivariate stepwise regression model was used to detect the relationship between Sestrin2 and other variable factors. The Sestrin2 levels were compared between before and after four weeks treatment by nasal continuous positive airway pressure (nCPAP) in severe OSA patients. Fifty-seven subjects were divided into two groups: control group (39.33 ± 9.40 years, n = 21) and OSA group (38.81 ± 7.84 years, n = 36). Plasma Sestrin2 levels increased in the OSA group (control group 2.06 ± 1.76 ng/mL, OSA group 4.16 ± 2.37 ng/mL; P=0.001). Sestrin2 levels decreased after four-week nCPAP treatment (pre-nCPAP 5.21 ± 2.32 ng/mL, post-nCPAP 4.01 ± 1.54 ng/mL; P=0.004). Sestrin2 was positively correlated with apnea/hypopnea index (AHI) oxygen desaturation index, while negatively correlated with mean oxygen saturation. Moreover, these correlations remained unchanged after adjusting for gender, age, waist-to-hip ratio, and body mass index. Multiple regression analysis showed that there was an association between Sestrin2 and AHI. Our findings suggest that Sestrin2 is involved in OSA. The increase of plasma Sestrin2 is directly related to the severity of OSA. To some extent, Sestrin2 may be useful for determining the severity of OSA and monitoring the effect of CPAP. In addition, since some complications of OSA such as coronary heart disease and diabetes are usually related with oxidative stress, the role of Sestrin2 in those OSA complications needs further study.